The Role of the Managerial Function of School Principals in Improving the Quality of Education Services - Fadillah, Reni; Madinah, Madinah; Liliana, Liliana; Syamsuriadi, Syamsuriadi (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims to: analyze the managerial role of school principals in improving the quality of education in elementary schools. This study uses a qualitative approach. The research subjects are principals and teachers.Methods of data collection using interviews, observation, and documentation. The data analysis technique uses qualitative data analysis from Miles and Huberman. The results of this study explain that the principal as a manager has the role of creating an organizational structure and inviting parents of students to the school committee program and completing the necessary supras; designing programs by outlining the needs of educators and teaching staff who carry out their duties, designing the curriculum that is implemented; supervising the output, teaching and learning process, and students from admission to completion; show a good and calm example at work, provide motivation and appreciation to its personnel both in terms of motile and material, involve educators and educators in training and education and motivate senior teachers to have the spirit of life long education;The obstacles faced are the lack of facilities and infrastructure in the teaching and learning process, there are still undisciplined educators and teaching staff, and the lack of communication between the principal and several educators and teaching staff. A good managerial principal will produce a good quality of education as well which of course will affect learning outcomes and school achievement. The results of this study indicate that a program is still needed to improve the quality of education, whether related to learning or not.